Creative Thinking Ability of Biology Teachers at State Senior High Schools in Pekanbaru - Febblina Daryanes; Riki Apriyandi Putra (AL-ISHLAH: Jurnal Pendidikan, 2022)
The teacher is one of the determinants of success in the learning process and the formation of the soft skills and hard skills of the students. If a teacher has the ability to think creatively and make decisions with a focus on improving higher-order thinking and is consistent over time, it is likely to be successful in training students' creative thinking skills. This study aims to analyze the level of creative thinking skills of Biology teachers at SMA Negeri Pekanbaru City. The population in this study were all Biology teachers in Pekanbaru City Senior High School, amounting to 62 people. The sampling technique used was saturated sampling. Data was collected using questionnaires and interview guidelines, the questionnaire was compiled based on 4 indicators of creative thinking developed by Marzano. The questionnaire data was analyzed by calculating the percentage and then interpreted into several categories, while the results of the interviews were analyzed qualitatively. The results showed that the level of creative thinking skills of Biology teachers in Pekanbaru City High School was 81.35%. The indicator of creative thinking ability, namely "developing new ways" is the indicator with the highest achievement, which is 83.1%. The indicator of creative thinking ability "setting personal standards" has the lowest achievement among other indicators, which is 78.7%. Teachers who have been teaching for more than 20 years achieved very good categories on the indicators of “maximizing skills and knowledge” and “setting and using personal standards”. From the results of the study, it can be concluded that the level of creative thinking of Biology Teachers in Pekanbaru City Senior High School is in the good category